Pendugaan Area Kecil Tingkat Pengangguran Terbuka Level Kecamatan Di Provinsi Kepulauan Riau Tahun 2022 - Puspita, Desak Nyoman Febrina Ambara; Ubaidillah, Azka (Politeknik Statistika STIS, 2024)
Kepulauan Riau is the province with the second highest Unemployment Rate (TPT) in 2022. Kepulauan Riau’s TPT has doubled In last decade. It was 5,08 percent in August 2012 to 10,34 percent in August 2020. Kepulauan Riau has 31,8 percent of desperate unemployment. Unemployment alleviation policy is more efficient if it is focused on sub-districts area. However, TPT is available up to district level. Sakernas August 2022 does not have sufficient sample size to estimate TPT in the sub-district level. Therefore, this study aims to estimate TPT at sub-district level in Kepulauan Riau in 2022 using Small Area Estimation (SAE) with additional information from the Potensi Desa 2021. The results showed that Hierarchical Bayes Beta SAE produced sub-district TPT estimators with smaller relative standard errors than direct estimation. Sub-districts with high TPT values in Kepulauan Riau are spread in urban areas so that they require special policies in reducing unemployment.